Mycobacterium fortuitum cutaneous infection from amateur tattoo - Saroj Suvanasuthi (2018)
A case of cutaneous Mycobacterium fortuitum infection after receiving an amateur tattoo is reported. A few days after tattooing, an otherwise healthy 25-year-old Thai male presented with multiple discrete erythematous papules confined to the tattoo area. He was initially treated with topical steroid and oral antihistamine without improvement. Skin biopsy was carried out, and the histopathology showed mixed cell granuloma with a foreign body reaction (tattoo color pigments). The acid-fast bacilli stain was positive. The tissue culture grew M. fortuitum two weeks later. He was treated with clarithromycin 1,000 mg/day and ciprofloxacin 1,000 mg/day for 10 months with complete response. From the clinical aspect, tattoo-associated rapidly growing mycobacterium infection might be difficult to differentiate from the pigment-based skin reactions. Skin biopsy for histopathology and tissue culture for Mycobacterium probably will be needed in arriving at the diagnosis.